Fabrication of microenvironments with different geometrical features for cell growth studies - Avila, O. I.; Otuka, A. J G; Tribuzi, V.; Freitas, L. M. [UNESP]; Serafim, R. B. [UNESP]; Moraes, M. H.; Espreafico, E. M.; Valente, V. [UNESP]; Fontana, C. R. [UNESP]; Mendonça, C. R. (My University, 2014)
Studies of cell development in artificial microenvironments can contribute to understanding a series of physiological mechanisms that might be influenced by geometrical features of the microenvironment itself. In this work we applied two-photon polymerization to fabricate three-dimensional microenvironments composed of a matrix arrangement of microstructures (circular and square cross-sections pillars) with distinct spacing. Such microenvironments were used to evaluate the growth of Michigan Cancer Foundation-7 (MCF-7) cells that are commonly used as a model system to investigate fundamental aspects of the tumor biology. Our results reveal that the cell density decreases as the distance between structures in the environment is increased. Additionally, cell growth shows slightly better results for the microenvironments composed of circular cross-section structures.
Keywords: Green Fluorescent Protein; Michigan Cancer Foundation-7; Microfabrication; Photopolimerization; Two-photon absortion